3D printer emissions elicit filament-specific and dose-dependent metabolic and genotoxic effects in human airway epithelial cells - Barnett, LMA; Zhang, Q.; Sharma, S.; Alqahtani, S.; Shannahan, J.; Black, M.; Wright, C. (Frontiers in Public Health, 2024)
Three-dimensional (3D) printers have become popular educational tools in secondary and postsecondary curriculum; however, inhalation exposure concerns and potential health risks have emerged. Current evidence suggests filament materials and site conditions may cause differences in chemical profiles and toxicological properties of 3D printer emissions; however, few studies have evaluated exposures directly within schools. In this study, we monitored and sampled particulate matter (PM) emitted from acrylonitrile-butadiene-styrene (ABS) and polylactic acid (PLA) filaments during a 3-hour 3D printing session in a high school classroom using aerosol monitoring instrumentation and collection media. To evaluate potential inhalation risks, Multiple Path Particle Dosimetry (MPPD) modeling was used to estimate inhaled doses and calculate in vitro concentrations based on observed aerosol data and specific lung and breathing characteristics.Dynamic light scattering (DLS) was used to evaluate the hydrodynamic diameter, zeta potential, and polydispersity index (PDI) of extracted PM emissions dispersions. Small airway epithelial cells (SAEC) were employed to determine cellular viability, genotoxic, inflammatory, and metabolic responses using MTS, ELISA, and high-performance liquid chromatography-mass spectrometry (HPLC-MS), respectively. Aerosol monitoring data revealed emissions from ABS and PLA filaments generated similar PM concentrations within the ultrafine and fine ranges.However, DLS analysis showed differences in physicochemical properties of ABS and PLA PM, where the hydrodynamic diameter of PLA PM was greater than ABS PM, which may have influenced particle deposition rates and cellular outcomes. While exposure to both ABS and PLA PM reduced cell viability and induced MDM2, an indicator of genomic instability, PLA PM alone increased gamma-H2AX, a marker of double-stranded DNA breaks. ABS and PLA emissions also increased the release of pro-inflammatory cytokines, although this did not reach significance. Furthermore, metabolic profiling via HPLC-MS and subsequent pathway analysis revealed filament and dose dependent cellular metabolic alterations. Notably, our metabolomic analysis also revealed key metabolites and pathways implicated in PM-induced oxidative stress, DNA damage, and respiratory disease that were perturbed across both tested doses for a given filament.Taken together, these findings suggest that use of ABS and PLA filaments in 3D printers within school settings may potentially contribute to adverse respiratory responses especially in vulnerable populations.